An Evaluation of the Effectiveness of the National Aeronautics and Space Administration Mission-X Child Health Promotion Program in the United States. Issue 6 (July 2018) - Min, Jungwon; Tan, Zhengqi; Abadie, Laurie; Townsend, Scott; Xue, Hong; Wang, Youfa
Purpose: To examine the effects of the National Aeronautics and Space Administration Mission-X: Train Like an Astronaut program (MX) on children's health-related knowledge and behaviors of a sample of US participants. Design: A nonexperimental pilot intervention study in 5 cities with a pre–post comparison of children's health-related knowledge and behaviors in the United States in 2014 and 2015. Sample: Children (n = 409) with a mean age (standard deviation) of 10.1 (1.7) years. Measures: Children answered pre- and postintervention questionnaires. We measured the differences in children's health knowledge on nutrition and physical fitness and behaviors on diet and physical activity as scores. Intervention: A 6-week web- and school-based intervention for a healthier lifestyle by introducing physical fitness and science activities based on actual astronaut training under a teacher's supervision. Analysis: Nonparametric analysis and logistic regression models. Results: Participants significantly improved both of their health behaviors on physical activity ( P < .001) and diet ( P = .06) and their health knowledge regarding nutrition ( P < .001) and physical fitness ( P < .001) after the intervention. The improvement in children's behaviors ( P < .001), knowledge ( P < .001), and the total score ( P < .001) after intervention did not significantly vary by sex or age, after adjusting for year of participation and state of residency. Discussion: The MX seems effective in improving health behaviors and health knowledge of participating children, which may serve as a model for sustainable global child health promotion program. Further research is needed to test its long-term effects on child health.